Pengaruh Penanaman Modal Dalam Negeri (PMDN) Dan Penanaman Modal Asing (PMA) Terhadap Produk Domestik Regional Bruto Di Provinsi Sumatera Utara Tahun 2010-2020 - Yuni Sartika Br Manalu; Dea Novika; Rettyani Ganumba (Fakultas Ekonomi dan Bisnis Universita Labuhanbatu Sumatera Utara Indonesia, 2022)
One of the important benchmarks in determining the success of economic development is economic growth that describes a real impact of development policies implemented, an indicator commonly used to measure the economic growth of a region is the Gross Regional Domestic Product (GRDP). The greater domestic investment such as investment is expected to encourage the growth of the private sector and households in allocating resources in an area. The existence of external sources of funds (foreign capital) can be utilized by developing countries as a basis for accelerating investment and economic growth. The purpose of this study is to determine the effect of domestic and foreign investment on GDP of North Sumatra. In this study using the type of secondary data, which is quantitative in the form of time series data (time series data). The data needed is data on domestic investment (PMDN), Foreign Investment (PMA), Gross Regional Domestic Product (GRDP) in North Sumatra in 2010-2020. The results of this study indicate that the PMDN has a positive and significant effect on the GDP of North Sumatra. Similarly, the variable PMA can be concluded also that PMA has a positive and significant effect on GDP in North Sumatra.